Linguistic Politeness in YouTube Content by CXO Media: The Edition on Seizing Opportunities to Build Success - Aziz, Zeidtry Maulana (CV. Publikasi Indonesia, 2024)
This research aims to discuss the application of language politeness in digital communication on the YouTube platform, with a focus on the CXO Media channel. In interactions on social media, especially YouTube, language politeness plays an important role in maintaining a harmonious relationship between content creators and audiences, as well as reflecting social and cultural values. Based on Leech's theory of politeness, this study analyzes the five main maxims of wisdom, generosity, praise, humility, and agreement to identify the politeness strategies used in YouTube content. Through a qualitative approach with a look and note method, the results of the study show that the application of language politeness not only increases the effectiveness of communication, but also creates a positive environment and supports constructive audience engagement. So that the results were obtained that the data examples include appreciative remarks and personal experiences shared by creators, which are able to strengthen the positive image and loyalty of the audience. This research contributes to the understanding of the importance of language ethics in digital communication which is rapidly developing in the era of social media.